Efektivitas Musyawarah Perencanaan Pembangunan Dalam Mengakomodasi Aspirasi Masyarakat Pada Perencanaan Pembangunan Kota Gorontalo - Maniani, Gracella Stefani Deane; Paputungan, Ibrahim; Pangeran, Fatmawati; Hadjarati, Siti Fadillah (JPS: Journal of Publicness Studies, 2026)
This study aims to analyze the effectiveness of the Development Planning Deliberation in accommodating community aspirations in development planning in Gorontalo City. The research focuses on the implementation of the Development Planning Deliberation, the level of effectiveness in accommodating community aspirations, and the supporting and inhibiting factors affecting its implementation. This study employed a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation at the Regional Development Planning Agency, district offices, and village offices in Gorontalo City. Data analysis used an interactive model consisting of data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of the Development Planning Deliberation has been conducted according to regional development planning procedures; however, substantively it has not been fully effective in accommodating community aspirations. The realization rate of community proposals remains relatively low compared to the number of submitted proposals, indicating a gap between public aspirations and regional development policies. Supporting factors include clear regulations, commitment from the local government, and the availability of participatory forums. Meanwhile, inhibiting factors include limited regional budgets, low community capacity in formulating proposals, elite domination in decision-making processes, and lack of transparency in proposal selection. This study concludes that strengthening community participation and improving transparency are necessary to enhance the effectiveness of the Development Planning Deliberation in Gorontalo City.